2014
DOI: 10.1186/1754-6834-7-91
|View full text |Cite
|
Sign up to set email alerts
|

The JatrophaFT ortholog is a systemic signal regulating growth and flowering time

Abstract: Background: Jatropha curcas is being promoted as a new bioenergy crop in tropical and subtropical regions due to its high amount of seed oil and its potential capacity to grow on marginal land for biofuel production. However, the productivity of the plant is constrained by the unfavorable flowering time and inflorescence architecture, which render harvesting of seeds time-consuming and labor-intensive. These flowering-related traits have limited further widespread cultivation of Jatropha.Results: We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
(45 reference statements)
0
31
1
Order By: Relevance
“…Therefore, the JcLFY -overexpression transgenic lines used in this work showed a slightly early flowering, but weaker phenotype than plants overexpressing the Arabidopsis LFY gene in Arabidopsis 27 and citrus31. The early flowering phenotype of JcLFY transgenic Jatropha was also weaker than observed in studies of transgenic Jatropha plants overexpressing the florigen gene JcFT 4142, in which flower buds initiated directly from transformed callus 7 weeks after in vitro culture47. However, the JcLFY co-suppressed transgenic Jatropha plants did not exhibit late flowering (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, the JcLFY -overexpression transgenic lines used in this work showed a slightly early flowering, but weaker phenotype than plants overexpressing the Arabidopsis LFY gene in Arabidopsis 27 and citrus31. The early flowering phenotype of JcLFY transgenic Jatropha was also weaker than observed in studies of transgenic Jatropha plants overexpressing the florigen gene JcFT 4142, in which flower buds initiated directly from transformed callus 7 weeks after in vitro culture47. However, the JcLFY co-suppressed transgenic Jatropha plants did not exhibit late flowering (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…The existence of a lengthy juvenile phase in woody species is a limiting factor for their genetic improvement, and this prevents the full domestication of many economically important woody species. Currently, only Jatropha FLOWERING LOCUS T ( JcFT )4142, and JcAP1 43 have been functionally analyzed in Jatropha . However, cloning and molecular characterization of JcLFY has not yet been reported.…”
mentioning
confidence: 99%
“…[55 ]. Expression of Jatropha JcFT under the control of the relatively weak synthetic G10-90 promoter reduced flowering time from 8 months to 1-2 months and induced early flowering in non-transgenic scions (Figure 3).…”
mentioning
confidence: 96%
“…Whichever mechanism is used to respond to different photoperiods, the main output of the interaction between the circadian clock and the light cues is the regulation of a CONSTANS -like factor that tightly control the expression of a FT- like gene, whose gene product is commonly known as the florigen (reviewed in Golembeski et al ., 2014; Song et al ., 2015). The ectopic expression or down-regulation of FT -like genes in a broad range of plant species have demonstrated that FT -like genes act as universal promoters of flowering (Endo et al 2005, Böhlenius et al 2006, Hsu et al 2006, 2011, Tränkner et al 2010, Fu et al 2014, Ye et al 2014, Freiman et al 2015, Klocko et al 2016).…”
Section: Introductionmentioning
confidence: 99%